Temperature dynamics interference measuring in solid-state acoustooptical modulators - Andrey Belousov; Peter Belousov; Leonid Borynyak (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is determined by the necessity of solid-state acoustooptical modulators effective using in a wide range of technical devices such as deflectors, frequency shift setups, sweeping tools, optical beam splitters, laser Doppler anemometers et cetera. The main aim of the study: investigation of temperature dynamics in solid-state acoustooptical modulators by non-invasive optical methods; substantiation of solid-state acoustooptical modulators switching mode using in devices; estimation of applicability range and possible operating biases. The methods used in the study: measurement of light wave phase shift induced by solid-state acoustooptical modulator active area geometrical characteristics and optical density thermal alterations. Estimation of temperature integral changing depending on time and interrogation beam location in acoustic transmission duct. A two-beam interferometer was used. Helium-neon laser emission with wavelength λ=632,8 nm and power 0,5 mW was divided into two rays by beam splitting cube. The acoustooptical modulator was placed in one of the beams. A phase shift produced by geometric parameters of investigated object and optical density changings was determined by interference fringe shift. Methods of image analysis, interferometry, photometry, acoustooptics, material science, coherent optics, laser physics. The results: The authors have measured the light wave phase shift caused by alterations of optical density and object thickness. Temperature integral change was estimated depending on time and probing beam location in acoustic transmission duct of acoustooptical modulator. The warm-up period of optical modulator was defined. The findings revealed that measuring maximal error magnitude of flow velocity with low event's frequency of light-diffusing tracers for solid-state acoustooptical modulator switching mode would equal 0,5 %. The measurement accuracy can be increased by usage of error correction algorithms.